E-competencies and Digital Skills Training: Principles for Developing Teaching Methods (Case of Russia and Kazakhstan) - Anna SHEVYAKOVA; Elena PETRENKO; Sergey MANAKHOV (Communications of International Proceedings, 2021)
The article reveals the possible changes and requirements in Russia and Kazakhstan for the formation of E-competencies by the active digitalization of the global economy. All employees in one way or another are affected by new information and communication technologies (ICT) and have to deal with the changing requirements of constantly evolving technology. This requires a new set of skills, some of which are unknown to employees. In this context, it is all the more important to prepare current and future employees for this changed environment by providing appropriate training and development. This article provides suggestions for suitable training methods that have been developed and is presented as a Draft Guide that can be used in other countries as well. It is necessary to emphasize the need to institutionalize the tasks of maintaining and using the results achieved and to stimulate appropriate proposals. The findings are of undoubted interest in the context of the global pandemic and the transition of company employees to distance work.
Keywords: Russia; Kazakhstan; E-competencies; digitalization; distance learning; educational institutions; E-Learning; digital technologies; IT professionals; digital competencies; mass open online courses.